Pediatric Hodgkin's lymphoma presenting with pseudo-achalasia and para-neoplastic neurological syndrome (Guillain-Barre): A case report - Ramy Mohamed Ghazy (Elsevier, 2017)
Introduction: Pseudo-achalasia (secondary achalasia): is a disorder produced by tumor at or near the gastro-esophageal junction, resulting in manifestation similar to those produced by achalasia. Dysphasia, regurgitation, and weight loss are the main presenting symptoms. Hodgkin's lymphoma is associated with multiple para-neoplastic neurological syndromes, of which demyelinating polyneuropathies are very unusual. Para-neoplastic neuropathies are difficult to diagnose, especially when they are the presenting features. Case presentation: We report a rare case of 11years old child who presented with pseudo-achalasia and Guillain-Barre syndrome, eventually diagnosed as Hodgkin's lymphoma. Conclusion: Hodgkin's lymphoma can present with pseudo-achalasia and may be associated with para-neoplastic neurological syndrome's.